Review of female Andreimyrme Lelej (Hymenoptera: Mutillidae: Smicromyrmini) - Okayasu, Juriya; Williams, Kevin A.; Lelej, Arkady S.; Pham, Thai Hong (Zootaxa, 2021)
Females of the East Asian velvet-ant genus Andreimyrme Lelej, 1995 are reviewed. The genus definition is extended to accommodate A. borkenti (Williams, 2019), comb. nov. (from Smicromyrme Thomson, 1870), and nine new species: A. auricoma Okayasu, sp. nov. (Malaysia), A. laminatihumeralis Okayasu, sp. nov. (Indonesia, Malaysia), A. matsumotoi Okayasu, sp. nov. (Vietnam), A. naturalis Williams, sp. nov. (Indonesia), A. rong Williams, sp. nov. (Thailand, Vietnam), A. silvorientalis Okayasu, sp. nov. (Indonesia), A. takensis Okayasu, sp. nov. (Thailand), A. ursasolaris Williams, sp. nov. (Indonesia), and A. yotoi Okayasu, sp. nov. (Laos, Vietnam). Diagnoses, distributional records, and illustrations are provided for these and four previously recognized species, A. neaera (Mickel, 1935), A. paniya Terine, Lelej & Girish Kumar, 2021, A. sarawakensis Lelej, 1996, and A. substriolata (Chen, 1957). Andreimyrme borkenti is newly recorded from Vietnam. A key to species known from females is provided. Habitat preference of this genus is discussed based on collecting records.